RASIO CAMEL SEBAGAI ALAT UKUR TINGKAT KESEHATAN BANK SWASTA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Andayani, Sari (Journal of Accounting and Strategic Finance, 2010)
Indonesia's banking industry is very crucial role in the economy, this is because banking is one of the financial system that serves as the Financial Intermediary, which is an institution that has a role to bring together the owners and users of funds. Along with multi-dimensional crisis that has hit Indonesia since mid-1997 that began with the falling value of the rupiah against the U.S. dollar has been destroyed joints in the economy including the banking sector. One of the effects of the monetary crisis that hit Indonesia was the collapse of the banks because they are no longer feasible to continue the business Research variables include Capital Adequacy Ratio, risked Return On Assets, Net Profit Margin, Return on Assets, Operating Expenses to Operating Income, and Banking Ratio. Which made the population in this study are 25 listed private bank in Indonesia Stock Exchange. Analytical model used to test the proposed hypothesis is discriminant analysis. From the test results is known that the hypothesis that there are differences in average significantly to the health of public banks, as measured by CAMEL ratios between healthy banks with banks that fail can be tested truth. Keywords: CAMEL ratios, Level of Bank Health